A multi-isotopic geochemical investigation of the Lower Zone, Bushveld Complex, South Africa: implications for a crustal component for parental magmas - Edwards, Hunter R (Department of Geological Sciences, 2021)
The current study focuses on the Lower Zone of the Bushveld Complex, South Africa using multiple geochemical and isotopic systems to determine the origin of crustal signatures, i.e. crustal assimilation or recycled crust in the mantle source, present throughout the Rustenburg Layered Suite (RLS) such as elevated  18O values. These geochemical and isotopic systems include major elements, trace elements, highly siderophile elements, oxygen isotopes, 87Sr/86Sr, 143Nd/144Nd, and Os-Os isotopes. Samples come from the Nooitgedacht Borehole 2 (NG2) at Union Section of the western limb of the Bushveld Complex, which sampled the Lower Zone. The 87Sr/86Sri (0.7043 – 0.7086) and Ndi values (-7.40 - -4.97) calculated in this study are in agreement with published data for the Bushveld. The majority of NG2 samples contain  18O greater than mantle peridotite (5.50‰) and MORB (5.70‰), in which NG2  18O ranges from 5.60 up to 8.00‰ for olivine, orthopyroxene, and clinopyroxene separates. These high  18O values suggests the Bushveld magmas sourced a crustal reservoir, either through crust assimilation or recycled crustal materials in the mantle source. This is the first study utilizing the Re-Os isotope system for the Lower Zone. The Osi values for the NG2 suite range from -4.37 to +35.9, which overlap with published data for the Critical Zone and the Platreef, the only previous Re-Os studies on the Bushveld. However, there are no previously reported negative Osi values for the Bushveld. The range in Osi values for the NG2 samples suggest mixing of at least two geochemical reservoirs. In addition to Lower Zone NG2 samples, sample NG2-773.65 is a chilled margin sample at the base of the NG2 borehole that contains high  18O ( 18O = 9.42 – 9.78‰) and radiogenic Osi (Osi = +62.5), in which the crust and/or recycled crust in the mantle source caused these high values. Sample NG2-734.64 contains the second lowest  18O ( 18O = 5.67‰) and most unradiogenic Osi (Osi = -4.37) values for the NG2 suite, evidence for a harzburgitic SCLM (H-SCLM) mantle source component. A lack of correlations for Osi values with  18O and 87Sr/86Sri values are indices for crustal assimilation processes. This lack in correlation may suggest a crustal component in the mantle is more likely than assimilation of the crust during ascent of the magmas toward the surface. The geochemical data presented in this study suggest the Lower Zone parent magma had a H-SCLM mantle source component in addition to the assimilation of the crust and/or the eclogitic SCLM (E-SCLM).